HUBUNGAN STRES KERJA DAN BEBAN KERJA DENGAN KECERDASAN EMOSI GURU SLB DI KABUPATEN BATANG - Amelia Putri Nirmala; Fatul Hikmah (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to determine the relationship between work stress and workload on the emotional intelligence of teachers at SLB Negeri Batang. There are two hypotheses proposed in this study, namely the minor hypothesis There is a negative relationship between work stress on emotional intelligence in special school teachers, meaning that the higher emotional intelligence the lower the work stress, and there is a negative relationship between workload on emotional intelligence in special school teachers, meaning that the higher the emotional intelligence, the lower the work stress. The higher the workload, the lower the emotional intelligence. The major hypothesis is a hypothesis that includes the relationship between all variables and all research objects. Which means that there is a relationship between work stress and workload on the emotional intelligence of teachers at SLB Negeri Batang. The subjects of this study were SLB Negeri Batang teachers as many as 28 teachers. The sampling technique is saturated, which means that all populations are sampled. Collecting data using a Likert scale, namely emotional intelligence, work stress, and workload. The results of the major hypothesis test show that the significance value of F charge is 0.000 <0.05 and the value of R = 810, which means that there is a very strong significant relationship between work stress and workload. while the value of R square = 0.657, this means that there is a contribution from the work stress and workload variables of 60% to emotional intelligence. Keywords: Emotional Intelligence, Work Stress, Workload, Teacher, Special School